Complex Epithet Constructions: The North-Eastern Yakut Olonkho Telling Tradition - Efimova, Ludmila Stepanovna; Pavlova, Olga Ksenofontovna (Journal of History Culture and Art Research, 2019)
The present article describes complex epithet constructions, which were distinguished in the north-eastern Yakut Olonkho-telling tradition. The aim of the research is to study complex epithet constructions: epithets of comparison, numerical, and metaphoric epithets. There were a total of 251 (26%) epithets with complex comparisons found in the text in the course of its analysis. The first group comprises of epithets connected with natural objects. In Olonkho, the descriptions of the northern Yakutia territory (i.e., its plant life, water landscapes, general landscapes, and celestial events) are introduced by incorporating these epithets, which are widely used. The second group of complex epithets with comparisons comprises of somatic epithets which give a general description of the main and secondary characters through the body and appearance description as well as the gestures and emotions. The third group comprises of complex epithets, the objects of which are connected with dwellings, household dwellings, and general household features. A significant meaning of the bogatyr (ancient warrior) horse in the life of the main characters of Yakut Olonkho allows singling out a separate, the fourth group of epithets, i.e., 15 complex epithets, the objects of which are those denoting horse body parts. The north-eastern Olonkho text contained 382 instances of numbers used as component-parts of numerical epithets. The numerical epithets are subdivided into three groups. Thus, the first group, which is the largest among all three (91%) consists of numerical epithets, which in turn, include linear numerals as well as cardinal numerals and ones denoting age and number adverbs. The second group contains a smaller scope of numerical epithets (7%); these include numerical epithets based on the usage of double-digit numbers. The third and the smallest group (2%) includes numerical epithets which contain three-digit components (2%). Numerical epithets are one of the widely used epithets in the poetic structure of the epic tradition under study. Apparently, the numerals in this type of epithet constructions performed not only a comprehensive and descriptive but also an educational function. Metaphoric epithets make up 15% of the total amount of epithets identified and selected within the scope of the north-eastern Olonkho text research. They are equally simple and complex in their essence. Simple metaphoric epithets consist of one object and image. Complex epithets contain several objects, each of which has its own attributive combinations; these attributive combinations consist of a noun in its non-transferred meaning and a metaphor. Thus, epithets represented in the Olonkho texts are complex in their structure (26%).